2019
DOI: 10.1515/pac-2019-1007
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the chemistry of bicyclo- and 1-azabicyclo[1.1.0]butanes

Abstract: Bicyclo[1.1.0]- and 1-azabicyclo[1.1.0]butanes are structurally unique compounds that exhibit diverse chemistry. Bicyclo[1.1.0]butane is a four-membered carbocycle with a bridging C(1)-C(3) bond and 1-azabicyclo[1.1.0]butane is an analog of bicyclo[1.1.0]butane featuring a nitrogen atom at one bridgehead. These structures are highly strained, allowing them to participate in a range of strain-releasing reactions which typically cleave the central, strained bond to deliver cyclobutanes or azetidines. However, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 113 publications
0
22
0
Order By: Relevance
“…Previously, our group studied the preparation of (bicyclo[1.1.0]­butan-1-yl)­alkylamines 1 and their thermal and transition metal-catalyzed conversions to five-, six-, and seven-membered heterocycles such as 2 and 3 . ,, Other noteworthy discoveries in the field include enantioselective routes to bicyclo[1.1.0]­butanes 5 , diastereoselective additions to substituted cyclobutanes 7 and 10 , and insertions to access 2,2-dihalobicyclo[1.1.1]­pentanes 12 (Scheme ). Very recently, and independent of our concomitant studies, Gregson et al disclosed strain-release semipinacol rearrangements of isoelectronic azabicyclo[1.1.0]­butyl carbinols 14 toward azetidines 15 …”
mentioning
confidence: 73%
“…Previously, our group studied the preparation of (bicyclo[1.1.0]­butan-1-yl)­alkylamines 1 and their thermal and transition metal-catalyzed conversions to five-, six-, and seven-membered heterocycles such as 2 and 3 . ,, Other noteworthy discoveries in the field include enantioselective routes to bicyclo[1.1.0]­butanes 5 , diastereoselective additions to substituted cyclobutanes 7 and 10 , and insertions to access 2,2-dihalobicyclo[1.1.1]­pentanes 12 (Scheme ). Very recently, and independent of our concomitant studies, Gregson et al disclosed strain-release semipinacol rearrangements of isoelectronic azabicyclo[1.1.0]­butyl carbinols 14 toward azetidines 15 …”
mentioning
confidence: 73%
“…The bicyclo[1.1.0]butane ring system is a fascinating moiety since it is probably the most strained bicyclic compound (66.3 kcal mol À1 ). 14 As a result of its highly puckered conformation, both nucleophiles and electrophiles can engage in reaction with bicyclo[1.1.0]butanes. The nucleophilic addition of the Grignard reagent occurs along the axis of the 2p-orbitals forming the central bent s-bond, thus explaining the relative diastereoselectivity observed (see nucleophilic approach Scheme 2).…”
Section: Group 1: Carbon(s) Insertion Through Opening Of a Bicyclic Systemmentioning
confidence: 99%
“…As shown in selected examples, vinyl and alkyl groups efficiently rearranged to produce cyclobutylboronic ester (23,24). Grignard reagent was also used as a nucleophile to generate the atecomplex, while the addition of LiCl was essential (25). 8b They also reported that other cationic carbon electrophiles such as iminium salt and tropylium could be used in the reaction to give 26 and 27.…”
Section: Cyclopropanementioning
confidence: 99%
“…Because of this highly strained structure, the central carboncarbon σ-bond of bicyclo[1.1.0]butane is relatively weak and several unique reactions that proceed through scission of the σ-bond have been reported. 25 Recently, Aggarwal and coworkers reported a series of reactions exploiting a bicyclo[1.1.0]butylboronic ester scaffold. The general scheme for the 1,2-difunctionalization of bicyclo[1.1.0]butyl boronic ester ate-complex is depicted in Scheme 7.…”
Section: Bicyclo[110]butanementioning
confidence: 99%